Comparability of Digital Photography with the ETDRS Film Protocol for Evaluation of Diabetic Retinopathy Severity. (2011)
ABSTRACT: Purpose.: To evaluate digital photography parameters affecting comparability with the Early Treatment Diabetic Retinopathy Study (ETDRS) film protocol for diabetic retinopathy (DR) severity grading. Methods.: ETDRS protocol photographs and four variations of digital images (uncompressed stereoscopic, compressed stereoscopic, uncompressed monoscopic, and uncompressed monoscopic wide-angle mosaic) of 152 eyes were independently evaluated by using ETDRS classifications. Digital formats were compared to film and each other for agreement on severity level, DR presence at ascending threshold, presence of the DR index lesion, and repeatability of grading. Study parameters included image resolution sufficient to distinguish small lesions, color balancing of digital images to film, documenting essential ETDRS classification retinal regions, similar magnification, and supplementary green-channel viewing. Results.: The κ statistic was substantial or near substantial between all digital formats and film for classifying severity levels (κ = 0.59–0.62; κw [linear weighted] = 0.83–0.87). The distribution of DR levels in all digital formats was not significantly different from that of the film (Bhapkar test, P = 0.09–0.44). The κ among digital formats for severity level was also substantial or near substantial (κ = 0.58–0.76, κw = 0.82–0.92). Differences between digital formats and film for grading severity level, severity threshold, or index lesions were not significant. The repeatability of grading between readers using film and all digital formats was also similar. Conclusions.: Digital format variations compared favorably with film for DR classification. Translating film characteristics (resolution, color/contrast) and protocol (magnification, retinal regions) to digital equivalents and augmentation of full color with green-channel viewing most likely contributed to the results.